PENDIDIDIKAN EMANSIPATORIS DAN MASYARAKAT MADANI - Rukiyati Rukiyati; L. Andriyani L. Andriyani (Jurnal Cakrawala Pendidikan, 1999)
The civil society is basically a society which is dialogueorientedand emancipato~ya s well as independent in natuse.It is an arena where various social movements express themselvesin groups to proceed with their interests.'Fo come to such a society there needs to be a socialtransformation which involves, among others, education.All this time the educational realities in Indonesia have notheen adequate fol the formation of the cibil society. 1 herefore,there needs to be a refosniation of the educational pal adigmso that education which is emancipato~? iu nature isachieved. Habermas' theory of co~ununicationc an be onealternative means in the course of reforming the educationalparadigm in Indonesia.The imple~nentationo ft laber~nas't heory of communicationin education can be made in the teaching-learningprocess. This process demands the fulfillment of the claimsof communication concerning tr~1t1-r1i.g htness. sincerity, andcomprehensibility. In the teaching-learning process whichfdfils the claims of comnlunication will appear the dimensionsof interest, discourse. consensus, and emancipationwhich bring the teacher and students together to a self-I eflection.